1964
DOI: 10.1099/00221287-34-2-259
|View full text |Cite
|
Sign up to set email alerts
|

The Carotenoids of Algae: Pigments from some Cryptomonads, a Heterokont and some Rhodophyceae

Abstract: SUMMARYThe carotenoids of two Cryptophytes, one heterokont and five Rhodophytes have been examined. The main pigments present are, in Cryptomonas sp., or-carotene and diatoxanthin ; in Hemiselmis virescens, a-carotene, and diatoxanthin ; in Vischeria sp., p-carotene and three unidentified xanthophylls ; in Antithamnion plumula and Nemalion multijidum, B-carotene, lutein and neoxanthin ; in Erythrotrichia carnea, Rhodosorus marinus and Polysiphonia fastigiata, p-carotene, zeaxanthin and lu tein .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

1967
1967
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 11 publications
3
19
0
Order By: Relevance
“…It is possible that the minor xanthophyll observed in Hemiselmis virescens Droop by Allen et al (1964) corresponds to one of the two minor xanthophylls listed as 3 and 4 in Table 1; the spectral data do not correspond sufficiently for an unequivocal assignment to be made. It is possible that the minor xanthophyll observed in Hemiselmis virescens Droop by Allen et al (1964) corresponds to one of the two minor xanthophylls listed as 3 and 4 in Table 1; the spectral data do not correspond sufficiently for an unequivocal assignment to be made.…”
Section: Cryptophytamentioning
confidence: 99%
See 2 more Smart Citations
“…It is possible that the minor xanthophyll observed in Hemiselmis virescens Droop by Allen et al (1964) corresponds to one of the two minor xanthophylls listed as 3 and 4 in Table 1; the spectral data do not correspond sufficiently for an unequivocal assignment to be made. It is possible that the minor xanthophyll observed in Hemiselmis virescens Droop by Allen et al (1964) corresponds to one of the two minor xanthophylls listed as 3 and 4 in Table 1; the spectral data do not correspond sufficiently for an unequivocal assignment to be made.…”
Section: Cryptophytamentioning
confidence: 99%
“…(2) This compound was designated diatoxanthin by Allen et al (1964) and 'probably zeaxanthin' by Haxo & Fork (1959). See text.…”
Section: Classmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the case of Cryptophyta algae an infrequent preponderance of a-carotene has been observed (Allen et al, 1964), while in Pheophyta neither a-carotene nor lutein have been detected.…”
Section: Carotenesmentioning
confidence: 96%
“…Recent workers (STRAIN 1958, CHAVMAN 1966 have shown that the only carotenoids found in the Rhodophyta are a-and fl-carotene, lutein and zeaxanthin, although earlier workers had reported finding taraxanthin (HEILBRON 1942, t-[EILBRON, PAR~Y & PHIPERS 1935 and neoxanthin (ALLEN et al 1964) in some species. ALLEN et al (1964, p. 268) state that "the main qualitative differences observed are the presence or absence of a-carotene and the presence or absence of zeaxanthin".…”
Section: Introductionmentioning
confidence: 99%